Determining Soft Layer Thickness Using Ambient Seismic Noise Record Analysis in Kota Baru, South Lampung - Ipmawan, Vico Luthfi; Permanasari, Ikah N. P.; Siregar, Rahmat Nawi (UI Scholars Hub, 2019)
The local site effect of an earthquake can be calculated through an analysis of short period ambient noise, known as microtremors. The fundamental frequency and amplification factors can be identified by analyzing microtremors using the Horizontal to Vertical Spectral Ratio (HVSR) method. This information can then be used to determine the thickness of the soft layers of sediment. This study analyzed microtremor recordings made in Kota Baru, South Lampung. The amplification factor range according to the HVSR method was 2.3 to 6.17, and the fundamental frequency range was 0.56 Hz to 1.46 Hz. Some spectrums exhibit two peaks with f0 > f1. We suggest that these locations have two layers with significant impedance contrast, which aligns with the geological conditions. The center of the Kota Baru area, especially the region around T11 and T15, has a thicker soft layer than the outskirts; in the central area, the soft layer is approximately 85 to 102 meters thick. The western part of the analyzed area has a shallower soft layer of about 32 to 46 meters. The analysis indicates that the western part has less amplification because it is shallower than the other parts of the analyzed region.